Correlation of serum BNP and ET-1 levels with cardiac pump function and ventricular remodeling in patients with heart failure - Qin, Limin; Liu, Xiaohong; Li, Yi (Cellular and Molecular Biology, 2020)
This study aimed to explore the correlation of serum brain natriuretic peptide (BNP) and endothelin-1 (ET-1) levels with cardiac pump function and ventricular remodeling in patients with heart failure. Eighty-one patients with chronic heart failure admitted to our hospital from March 2016 to November 2018 were enrolled as the study group, and 80 healthy individuals as the control group. Immunofluorescence was used for the detection of serum BNP, ELISA for serum ET-1, and ultrasound for related indexes of cardiac pump function and ventricular remodeling. Moreover, correlation analysis and prognostic factors analysis were carried out. Both BNP and ET-1 were highly expressed in the serum of patients with heart failure. Cardiac pump function related indexes (left atrial ejection fraction (LAEF), left atrial passive ejection fraction (LAPEF), and left atrial active ejection fraction (LAAEF)) in the study group were significantly lower than those in the control group (P< 0.05). While ventricular remodeling related indexes (left ventricular end-diastolic diameter (LVEDD), interventricular septum thickness (IVST), left ventricular posterior wall thickness (LVPM), and left ventricular mass index (LVMI) in the study group were significantly higher than those in the control group (P< 0.05). BNP and ET-1 were negatively correlated with LAEF, LAPEF and LAAEF (P< 0.05), and were positively correlated with LVEDD, IVST, LVPM and LVMI (P< 0.05). The expressions of serum BNP and ET-1 were higher in patients with cardiovascular events than those without cardiovascular events. Hypertension, hyponatremia, high BNP, high ET-1, NYHA classification, decreased LAEF and increased LVEDD were independent risk factors for cardiovascular adverse events. Serum BNP and ET-1 are closely related to cardiac pump function and ventricular remodeling in patients with heart failure and can be used as important reference indexes for prognosis evaluation.